2021
DOI: 10.1002/cne.25240
|View full text |Cite
|
Sign up to set email alerts
|

Co‐localization of nociceptive markers in the lumbar dorsal root ganglion and spinal cord of dromedary camel

Abstract: Nociceptive markers in mice have been identified in two distinct peptidergic and nonpeptidergic neurons in the dorsal root ganglion (DRG) and distributed in different laminae of the dorsal horn of the spinal cord. Recently, however, a study in humans showed a significant overlapping in these two populations. In this study, we investigated the distribution of various nociceptive markers in the lumbar DRG and spinal cord of the dromedary camel. Immunohistochemical data showed a remarkable percentage of total neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 78 publications
3
3
0
Order By: Relevance
“…In the present study, PNX + /nNOS-containing neurons formed the third largest (approximately 50%) population among all afferent cells capable of synthesizing and releasing PNX as their transmitter; the vast majority of these neurons were Sl-and M-sized cells. This is well in line with the data obtained in other species (humans, rats, mice, sheep, dromedary camels [20,[51][52][53]) where nitrergic afferent neurons were found in an average of 40-50% of all DRG cells, with the highest percentage in the subpopulation of Sl-and M-sized neurons. It should be emphasized that the high degree of nNOS co-localization with SP and CGRP, reported by Russo and colleagues [53], additionally supports the above hypothesis, suggesting the existence of a PNX + /SP + /CGRP + /NOS + population of DRG cells.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, PNX + /nNOS-containing neurons formed the third largest (approximately 50%) population among all afferent cells capable of synthesizing and releasing PNX as their transmitter; the vast majority of these neurons were Sl-and M-sized cells. This is well in line with the data obtained in other species (humans, rats, mice, sheep, dromedary camels [20,[51][52][53]) where nitrergic afferent neurons were found in an average of 40-50% of all DRG cells, with the highest percentage in the subpopulation of Sl-and M-sized neurons. It should be emphasized that the high degree of nNOS co-localization with SP and CGRP, reported by Russo and colleagues [53], additionally supports the above hypothesis, suggesting the existence of a PNX + /SP + /CGRP + /NOS + population of DRG cells.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies revealed that, CGRP, together with SP (see below), appears to be the "canonical" transmission molecule of afferent neurons in all mammalian species studied so far (human, horse, dromedary camel, pig, cat, rat and mouse) [16][17][18][19][20]. According to the available data, the proportion of sensory neurons containing CGRP (or expressing mRNA encoding this peptide [21,22]) ranging, on average, between 50 and 60% of all DRG cells, regardless of the species studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in previous studies, CGRP appears to be, together with SP (see below), the "canonical" transmission molecule of afferent neurons in all mammalian species studied so far (human, horse, dromedary camel, pig, cat, rat and mouse) [19][20][21][22][23]. According to the available data, the number of sensory neurons containing CGRP (or expressing mRNA encoding this peptide [24,25]) oscillates on average between 50 and 60% of all DRG cells, regardless of the species studied.…”
Section: Discussionsupporting
confidence: 55%
“…The above-mentioned close interdependence and cooperation of CGRP and SP in numerous regulatory loops seems to result from the fact that both substances coexist very often in the same sensory cell [17,20,23] from which they are released together and interact with target cells in a synergistic way, supporting each other. For example, as revealed by Biella and co-workers [35], the excitatory effects of SP arising from spontaneous and noxious activity were significantly enhanced by CGRP in the rat.…”
Section: Discussionmentioning
confidence: 99%